Kan regionalitet påvisas genom arkeologiskt fyndmaterial? Några metodiska och källkritiska närmanden. - Helgesson, Bertil (Hikuin, 2008)
Can regionality be pointed out through archaeological material? Some methodical and source critical aspects. By Bertil Helgesson The spread of archaeological and historical source material has been an important factor when discussing regional variations during the Iron Age and the Middle Ages in Southern Scandinavia. In this paper the conception of regionality is discussed and it is obvious that this may be expressed in many ways, depending on which historic problems are under discussion. The source material is, of course, an important variable but also social structure, social levels, natural geography, expressions in the periphery, anomalies and chronological duration. Regional studies on the basis of many categories of source material are necessary for understanding variations in landscape and society. Unfortunately there are too few of them. We must also be aware of the fact that the questions that we want to answer are basic and must be clearly expressed. These different variables are applied on an historical course of events, i.e. the province of Scania around 1000 A.D. It is obvious that different regions in Southern Scandinavia played different roles during the transition from the Viking Age into the Middle Ages. The rather neglected fact that medieval Denmark was united from Jelling, Jutland, might have been a more nuanced process seen in a regional context. The examination of the spread of source material can never be the goal of regional studies. The goal must be to express what the spread of the source material can tell us about landscape, social structure and human strategies. For this, more penetrating investigations are necessary involving several scientific disciplines.